REVITALISASI KAWASAN PECINAN SURYAKENCANA BOGOR SEBAGAI SEBUAH STRATEGI DALAM MENINGKATKAN CITRA KAWASAN - Ryan Salim; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
Suryakencana Street in the Suryakencana Chinatown Area, Bogor City is famous for its culinary delights. Although currently the culinary diversity in Suryakencana continues to grow, the presence of other culinary spots in Bogor has made Suryakencana's culinary name start to fade. To be able to restore and strengthen the image of the Suryakencana Area as a tourist visit route, new attractors are needed. The existence of the new attractor can improve the image of the Chinatown area, elevate Chinatown culture and make the Suryakencana area a culinary tourism area and Chinatown culture. The urban acupuncture method is used in selecting points that need to be